Under the cash pooling: does the cooperation matter? - San-Jose, Leire; Retolaza, Jose Luis (Business: Theory and Practice, 2019)
This paper presents comprehensive data on cash pooling between companies of the biggest cooperative corporation in Spain Mondragon Cooperative Corporation. The case study highlights financial phenomena using the concept of stakeholder theory based on management to create and generate value into the economy. Using Delphi technique combined with Cross-impact Matrix, we find that there are short and long variables necessary to an efficient cash pooling model: a mutual benefit based on trust is the main element but others as cycle and cooperation within managers’ skills are relevant, as well. Our results highlight that a high future positive expectation and the need for trust and mutual results in holding the cash are factors dissuading the isolation of a unique self benefit of the implicated companies.